Is uneven-aged silviculture best for maximizing ecosystem functioning, services, biodiversity, and resilience in Walloon forests? - Frédéric André; Arthur Guignabert; Hugues Goosse; François de Coligny; Gauthier Ligot; Benoit Courbaud; Mathieu Fortin; Mathilde Pau; Sylvain Marchi; Mathieu Jonard (Regional Environmental Change, 2026)

Continental Contrasts in Climate Extremes That Control Tree Fecundity - James S. Clark; Robert Andrus; Margarita Arianoutsou; Davide Ascoli; Yves Bergeron; Michal Bogdziewicz; Thomas Boivin; Raul Bonal; Thomas Caignard; Maxime Cailleret; Rafael Calama; J. Julio Camarero; et al. (Global Change Biology, 2026)
In 2023, more than half of olive harvests ( Olea europaea ) across Spain, Greece, and Türkiye were lost to drought. The same year late freeze destroyed 90% of the peach crop ( Prunus persica ) on the Georgia Piedmont and the apple crop ( Malus domestica ) in central New York, Vermont, and southern Quebec. Climate extremes now rank with the costliest threats to agriculture, but their role in forest recovery from diebacks that are happening globally is unknown for lack of tree fecundity estimates in forests. Tolerance of climate extremes could depend on past exposure but constrained by phylogenetic conservatism. We report a continental scale analysis of climate extremes and forest fecundity across North America and Europe showing that responses to late freeze and drought are happening now. Species differences are not explained by the traits typically included in ecological studies and they are weakly associated with phylogeny. Late freeze, that is, freezing temperatures that follow the onset of flower development in spring, is shown to be “normal” in North America, but not Europe, potentially explaining failed seed production due to delayed onset and the resultant shorter growing period by North American transplants dating back at least to the 18th century. Drought has thus far had the greatest impacts in dry forested regions, but here too, species differences are not explained by traditional trait values. If responses have been buffered from drought and late freeze by past exposure, acclimation and local adaptation prove inadequate as extremes intensify.

Corrigendum to “Oak regeneration facing deer browsing: Can competition between saplings offset the diversion effect? A simulation experiment” [Ecological Modelling 489 (2024) 110608] - Julien Barrere; Gauthier Ligot; Vincent Boulanger; Catherine Collet; Benoit Courbaud; François de Coligny; Anders Mårell; Sonia Saïd; Philippe Balandier (Ecological Modelling, 2025)

Corrigendum to “Spatial distribution of tree-related microhabitats in European beech-dominated forests” [Biol. Conserv. 301 (2025) 110867 10.1016/j.biocon.2024.110867] - Laurent Larrieu; Christophe Bouget; Benoit Courbaud; Inken Doerfler; Nicolas Gouix; Michel Goulard; Sylvie Ladet; Fabien Laroche; Amandine Acloque; Rita Bütler; Daniel Kozák; Daniel Kraus; et al. (Biological Conservation, 2025)

Spatial distribution of tree-related microhabitats in European beech-dominated forests - Laurent Larrieu; Christophe Bouget; Benoit Courbaud; Inken Doerfler; Nicolas Gouix; Michel Goulard; Sylvie Ladet; Fabien Laroche; Amandine Acloque; Rita Bütler; Daniel Kozák; Daniel Kraus; et al. (Biological Conservation, 2025)

The Relationship Between Maturation Size and Maximum Tree Size From Tropical to Boreal Climates - Valentin Journé; Michał Bogdziewicz; Benoit Courbaud; Georges Kunstler; Tong Qiu; Marie‐Claire Aravena Acuña; Davide Ascoli; Yves Bergeron; Daniel Berveiller; Thomas Boivin; Raul Bonal; Thomas Caignard; et al. (Ecology Letters, 2024)
The fundamental trade‐off between current and future reproduction has long been considered to result in a tendency for species that can grow large to begin reproduction at a larger size. Due to the prolonged time required to reach maturity, estimates of tree maturation size remain very rare and we lack a global view on the generality and the shape of this trade‐off. Using seed production from five continents, we estimate tree maturation sizes for 486 tree species spanning tropical to boreal climates. Results show that a species' maturation size increases with maximum size, but in a non‐proportional way: the largest species begin reproduction at smaller sizes than would be expected if maturation were simply proportional to maximum size. Furthermore, the decrease in relative maturation size is steepest in cold climates. These findings on maturation size drivers are key to accurately represent forests' responses to disturbance and climate change.

Linking seed size and number to trait syndromes in trees - Michal Bogdziewicz; Marie‐Claire Aravena Acuña; Robert Andrus; Davide Ascoli; Yves Bergeron; Daniel Brveiller; Thomas Boivin; Raul Bonal; Thomas Caignard; Maxime Cailleret; Rafael Calama; Sergio Donoso Calderon; et al. (Global Ecology and Biogeography, 2023)
Aim Our understanding of the mechanisms that maintain forest diversity under changing climate can benefit from knowledge about traits that are closely linked to fitness. We tested whether the link between traits and seed number and seed size is consistent with two hypotheses, termed the leaf economics spectrum and the plant size syndrome, or whether reproduction represents an independent dimension related to a seed size–seed number trade‐off. Location Most of the data come from Europe, North and Central America and East Asia. A minority of the data come from South America, Africa and Australia. Time period 1960–2022. Major taxa studied Trees. Methods We gathered 12 million observations of the number of seeds produced in 784 tree species. We estimated the number of seeds produced by individual trees and scaled it up to the species level. Next, we used principal components analysis and generalized joint attribute modelling (GJAM) to map seed number and size on the tree traits spectrum. Results Incorporating seed size and number into trait analysis while controlling for environment and phylogeny with GJAM exposes relationships in trees that might otherwise remain hidden. Production of the large total biomass of seeds [product of seed number and seed size; hereafter, species seed productivity (SSP)] is associated with high leaf area, low foliar nitrogen, low specific leaf area (SLA) and dense wood. Production of high seed numbers is associated with small seeds produced by nutrient‐demanding species with softwood, small leaves and high SLA. Trait covariation is consistent with opposing strategies: one fast‐growing, early successional, with high dispersal, and the other slow‐growing, stress‐tolerant, that recruit in shaded conditions. Main conclusions Earth system models currently assume that reproductive allocation is indifferent among plant functional types. Easily measurable seed size is a strong predictor of the seed number and species seed productivity. The connection of SSP with the functional traits can form the first basis of improved fecundity prediction across global forests.

Globally, tree fecundity exceeds productivity gradients - Valentin Journé; Robert Andrus; Marie‐Claire Aravena; Davide Ascoli; Roberta Berretti; Daniel Berveiller; Michal Bogdziewicz; Thomas Boivin; Raul Bonal; Thomas Caignard; Rafael Calama; Jesús Julio Camarero; et al. (Ecology Letters, 2022)
Lack of tree fecundity data across climatic gradients precludes the analysis of how seed supply contributes to global variation in forest regeneration and biotic interactions responsible for biodiversity. A global synthesis of raw seedproduction data shows a 250‐fold increase in seed abundance from cold‐dry to warm‐wet climates, driven primarily by a 100‐fold increase in seed production for a given tree size. The modest (threefold) increase in forest productivity across the same climate gradient cannot explain the magnitudes of these trends. The increase in seeds per tree can arise from adaptive evolution driven by intense species interactions or from the direct effects of a warm, moist climate on tree fecundity. Either way, the massive differences in seed supply ramify through food webs potentially explaining a disproportionate role for species interactions in the wet tropics.

Intra-specific variability and the competition–colonisation trade-off: coexistence, abundance and stability patterns - Benoit Courbaud; Ghislain Vieilledent; Georges Kunstler (Theoretical Ecology, 2012)